Gabriele Münter Preis '97 : 40 Künstlerinnen - Preisträgerin Valie Export. - Frauen Museum, Bonn; Kunsthalle Dominikanerkirche, OsnaBrück; Galerie am Fischmarkt, Erfurt; Badstübner-Gröger, Sibylle; Bell, Victoria; Benn, Gottfried; Berent, Hella; Bleyl, Matthias; Ficht, Wolfgang; Förster, Dr. Phil. Gerlinde; Gutbrod, Dr. Helga; Hiesl, Angie; et al. (Bonn : Frauen Museum, 1997)
Bahra, Alice ; Bell, Victoria ; Berent, Hella ; Bramke, Erdmut ; Busching, Claudia ; Dewes, Maria Anna ; Drebber, Magdalena ; Endriss, Lisa ; Export, Valie ; Goulbier, Yvonne ; Hammann, Barbara ; Heider, Gabriele ; Herhaus, Tallo ; Hiesl, Angie ; Hoffmann, Sabine ; Hoge, Annelise ; Jacobi, Ritzi ; Kallnbach, Siglinde ; Kaul, Christine ; Keusen, Ellen ; Klagge, Erika ; Löbner, Anna ; Lückerath, Ulla ; Maier, Veronika ; Ohlow, Eva ; Passow, Beate ; Perthen, Christine ; Perthen, Sigrid ; Pfaffenberger, Brigitte ; Rebmann, Margarete ; Roderburg, Johanna ; Rogenhofer, Sara ; Rosenbach, Ulrike ; Sakrowski, Karin ; Schreiber, Silvia ; Sigurdsson, Sigrid ; Song, Hyun-Sook ; Tralau, Marianne ; Weimer, Brigitta ; Wieckhorst, Karin
bibliografie
biografie
Gabriele Münter Preis '97 : 40 Künstlerinnen - Preisträgerin Valie Export, , Frauen Museum, Bonn, 11.06.1997 bis 28.09.1997 / Kunsthalle Dominikanerkirche, Osnabrück, 30.11.1997 bis 23.01.1998 / Galerie am Fischmarkt, Erfurt, 22.02.1998 bis 30.03.1998
Duits
boek